PENGARUH KOMUNIKASI ORGANISASI, MOTIVASI KERJA DAN KERJASAMA TIM TERHADAP KINERJA PEGAWAI - Ibnu Hajar; Salma Saleh (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
This research aims: 1) to study the effect of organizational communication, work motivation and teamwork on the performance of Wakatobi Regency DPRD Secretariat staffs, 2) to study the effect of communication on the performance of Wakatobi Regency DPRD Secretariat staffs, 3) to study the effect of work motivation on the performance of Wakatobi Regency DPRD Secretariat Staffs, 4) to study the effect of Teamwork on the performance of Wakatobi Regency DPRD Secretariat Staffs.The subject of this research is Wakatobi Regency DPRD Secretariat Staffs. The population of this research are all 30 civil servants (PNS) in the Wakatobi Regency DPRD Secretariat. The sample size used saturation sampling so the number of samples in this study is 30 people.The result shows that: 1) Simultaneously, organizational communication, work motivation and teamwork have significant effects on the performance of Wakatobi Regency DPRD Secretariat Staffs, 2) Communication has positive and significant effects on the performance of Wakatobi Regency DPRD Secretariat Staffs, 3) Work motivation has positive and significant effects on the performance of Wakatobi Regency DPRD Secretariat Staffs, 4) Teamwork has positive and significant effects on the performance of Wakatobi Regency DPRD Secretariat Staffs.Keywords: organizational communication, work motivation, teamwork, employees performance